2020
DOI: 10.3390/ijerph17061847
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microbiological Quality and Mycotoxin in Dried Chili by Morphological Identification, Molecular Detection, and Chromatography Analysis

Abstract: The growing interest in spicy foods leads to the global demand for spices, particularly dried chili. This study aimed to assay both aflatoxin (AFs) and ochratoxin A (OTA) contamination using an integrative method of morphological identification, molecular detection, and chromatography analysis on dried chili provided from traditional and modern markets in Indonesia. The results showed that total fungal infection ranged from 1-408 × 103 CFU/g. Eighty percent of the chili obtained from both the traditional and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Across all studies mentioned in Table 1, the average OTA concentration in liquorice was found in the range OTA in black pepper was found to be of a 'moderate occurrence' [4]. Across all studies mentioned in Table 2, the average OTA concentration was in the range of 0.34-155.00 ng g −1 [15,17,[23][24][25]27,[29][30][31]39,40,45] or was not detected at all [16,20,31,41,44]. In our study, the average OTA concentration of 0.31 ng g −1 in black pepper was not within the range found in the literature as it was found to be very similar, but slightly lower, than the OTA concentration of 0.0.34 ng g −1 in the Turkish study [39].…”
Section: Comparison Of Ota Results In Spices With Other Relevant Studies In the Worldmentioning
confidence: 99%
See 2 more Smart Citations
“…Across all studies mentioned in Table 1, the average OTA concentration in liquorice was found in the range OTA in black pepper was found to be of a 'moderate occurrence' [4]. Across all studies mentioned in Table 2, the average OTA concentration was in the range of 0.34-155.00 ng g −1 [15,17,[23][24][25]27,[29][30][31]39,40,45] or was not detected at all [16,20,31,41,44]. In our study, the average OTA concentration of 0.31 ng g −1 in black pepper was not within the range found in the literature as it was found to be very similar, but slightly lower, than the OTA concentration of 0.0.34 ng g −1 in the Turkish study [39].…”
Section: Comparison Of Ota Results In Spices With Other Relevant Studies In the Worldmentioning
confidence: 99%
“…OTA in chilli was found to be of a ‘moderate occurrence’ [ 4 ]. Across all of the studies mentioned in Table 1 , the average OTA concentration was found in the range of 0.62–97.10 ng g −1 [ 16 , 17 , 19 , 21 , 23 , 25 , 26 , 29 , 30 , 31 , 33 , 37 , 39 , 40 ], but it was not detected in another study [ 32 ]. In our study, both average OTA concentrations of 7.50 ng g −1 in milled chilli and 1.43 ng g −1 in crushed chilli with seeds were within the range found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest AFB 2 concentrations in different spices have been reported in chili (33.3 µg/kg) in Indonesia [ 113 ], paprika (9.9 µg/kg) in Italy [ 107 ], parsley (2.5 µg/kg) in Egypt [ 109 ], and fennel (2.3 µg/kg), turmeric (1.7 µg/kg) and coriander (1.6 µg/kg) in Malaysia [ 112 ].…”
Section: Mycotoxins and Microfungi In Spices From The Perspective mentioning
confidence: 99%
“…), one of the most important spice crops produced and consumed in many countries. Aflatoxin and OTA contamination are frequently detected in dried chili, with reported occurrences in multiple countries including Thailand (Tansakul et al, 2013), Sri Lanka, Belgium (Yogendrarajah et al, 2014), Pakistan (Iqbal et al, 2017), Nigeria, Ghana (Frimpong et al, 2019), and Indonesia (Wikandari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%